2017
DOI: 10.1021/acs.chemmater.6b04088
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Iron Nitride, ε-Fe3N: Preparation from Liquid Ammonia and Magnetic Properties

Abstract: e-Fe 3 N shows interesting magnetism but is difficult to obtain as a pure and single-phase sample. We report a new preparation method using the reduction of iron(II) bromide with elemental sodium in liquid ammonia at -78 °C, followed by annealing at 573 K. Nanostructured and monophasic oxygen-free iron nitride, e-Fe 3 N, is produced according to X-ray diffraction and transmission electron microscopy experiments. The magnetic properties between 2 K and 625 K were characterized using a vibrating sample magnetome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 50 publications
(102 reference statements)
5
33
0
Order By: Relevance
“…The Fe 3 N and Ta 5 N 6 crystals grown on other facets of substrates show polycrystalline features as further confirmed by X-ray diffraction (XRD) patterns (Figures S1 and S2, Supporting Information). [14] The single-crystalline structure is further confirmed by selected area electron diffraction pattern with a diameter of ≈1 µm in the inset of Figure 2a. Figure The crystalline structure of Fe 3 N single crystal is investigated using Cs-corrected scanning transmission electron microscopy (STEM) coupled with focused ion beam.…”
Section: Metallic Porous Single Crystalsmentioning
confidence: 67%
“…The Fe 3 N and Ta 5 N 6 crystals grown on other facets of substrates show polycrystalline features as further confirmed by X-ray diffraction (XRD) patterns (Figures S1 and S2, Supporting Information). [14] The single-crystalline structure is further confirmed by selected area electron diffraction pattern with a diameter of ≈1 µm in the inset of Figure 2a. Figure The crystalline structure of Fe 3 N single crystal is investigated using Cs-corrected scanning transmission electron microscopy (STEM) coupled with focused ion beam.…”
Section: Metallic Porous Single Crystalsmentioning
confidence: 67%
“…[20,21] It demonstrates the N-doping in carbond uring the nitridation process. [10] The peak at 707.3 eV is considered as metallic iron nitride (g'-Fe 4 N). [22,23] It is confirmed that the F-1 :2.5 600 contains ac ertain amount of carbon and furtherp rovest hat heteroatoms (O and N) are dopedi nto the Chem.E ur.J.2017, 23,17592 -17597 www.chemeurj.org carbon.I na ddition, the high-resolution Fe 2p spectrum is shown in Figure 5d.I tc an be clearly observed that the Fe 2p spectrum consists of five peaks:t he peaks at 710.0 and 713.0 eV are ascribed to Fe 2p 3/2 of Fe 2 + and Fe 3 + ,a nd the peaks at 724.5 and 726.4 eV are ascribed to Fe 2p 1/2 of Fe 2 + and Fe 3 + .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this iron oxide is an amorphous iron oxide.B ased on previousr eports, this amorphous iron oxide is iron monoxide (Fe 1-x O). [10] The peak at 707.3 eV is considered as metallic iron nitride (g'-Fe 4 N). [25] Additionally,t he XPS spectra of F-1 :2.5 580 and F-1 :2.5 620 are shown in Figure S5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations